EFL TEACHERS’ AND LEARNERS’ PERSPECTIVES ON THE PRINCIPLES OF INSTRUCTED LANGUAGE LEARNING: CONFLICT OR CONSENSUS? - Connor, Owen; Nazari, Ahmad (LLT Journal: A Journal on Language and Language Teaching, 2020)
The developmental nature of second language acquisition research has resulted in various and at times seemingly contradictory theories, methods and approaches. In 2005, Rod Ellis published his ?Principles of Instructed Language Learning,? which he considered to be a set of teaching ?generalisations? that could stimulate debate and reflection among teachers in the ?post-methods era? (Richards & Rodgers, 2014). The purpose of this study was to investigate Ellis?s principles in terms of their perceived relevance and applicability in an adult EFL learning environment. In order to achieve this aim, a mixed methods research approach was utilised. Separate questionnaires were administered to seventy-one students and eight teachers employed in the English Language Department of a Training Institute in Doha, Qatar. Additionally, thirteen students participated in two ? single sex ? focus group sessions. The results revealed consensus between students and teachers regarding the importance they placed on some principles, but not others, particularly the contentious issue of meaning vs. form. Furthermore, while both groups emphasised the importance of interaction, many students nonetheless felt uneasy interacting in English with other Arabic speakers. A further key finding was that neither party clearly understood the concept of the learner?s built-in syllabus. The principal conclusion is that the best way to deal with the aforementioned anomalies involves experimentation with task-based approaches as these allow for  a focus on meaning, opportunities for interaction, and a retrospective focus on form via corrective feedback, which takes into account the learner?s built-in syllabus.DOI: doi.org/10.24071/llt.2020.230105